Recurrent and Progressive Abdominal Pain and Enteritis in a Japanese Patient with Paroxysmal Nocturnal Hemoglobinuria - Akihisa Hino; Yukiko Yamashita; Mitsuhiro Yamaguchi; Yasuhiko Azenishi (Case Reports in Hematology)
This case report describes a young male patient with recurrent abdominal pain persisting for more than 16 months. Clinical investigations showed signs of inflammation and pancytopenia. A diagnosis of paroxysmal nocturnal hemoglobinuria (PNH) was made 9 months after the onset of the abdominal pain, following endoscopic examinations that revealed evidence of a previously unknown hemorrhage. Regular monitoring indicated that the abdominal pain was associated with elevations in lactate dehydrogenase, C-reactive proteins, and D-dimer levels. The patient started treatment with the complement inhibitor eculizumab shortly after it was approved for use in Japanese PNH patients with hemolysis. Resolution of the abdominal pain and normalization of clinical parameters were noted within 3 weeks from treatment initiation.